Effects of key parameters of straw chopping device on qualified rate, non-uniformity and power consumption - Wang, Weiwei; Li, Jincai; Chen, Liqing; Qi, Haijun; Liang, Xiutian (International Journal of Agricultural and Biological Engineering, 2018)
Mechanized straw return to field is a key component of conservation tillage in sustainable farming. The structural and movement parameters of straw chopping device have significant effects on qualified rate, non-uniformity, and power consumption during the operation. Sixteen types of straw chopping devices, including different key parameters (feeding speed, shell angle, distances of chopping and fixed blade), were compared using the field integrated testing system in harvested wheat field, and the effects of key parameters on qualified rate and power consumption under operating speed of 2000-3500 r/min were analyzed using finite element model (FEM). On the basis of orthogonal test, the effects of each factor on the qualified rate of wheat straw chopping and non-uniformity followed the descending order: feeding speed (significant), shell angle, distances of blades; and the qualified rate decreased with increasing feeding speed (n) and distances of the blades (L). The descending order of three factors’ effects on power consumption was shell angle (significant), feeding speed, distances of blade (not significant); and the power consumption decreased with increasing shell angle (α). The optimum performance parameters of straw chopping device were determined as follows: feeding speed 2500-3000 r/min, shell angle 65°-70°, distances of chopping and fixed blade 8-10 mm. The results showed that the qualified rate was 94.57%, non-uniformity was 11.12%, and power consumption was 5.23 kW. The results can provide a reference for optimal design of the straw chopping device to generate more suitable soil environments, and promote the application of the light seeding quality and operating efficiency. Keywords: straw chopping device, finite element analysis, qualified rate, non-uniformity, power consumption DOI: 10.25165/j.ijabe.20181101.3114 Citation: Wang W W, Li J C, Chen L Q, Qi H J, Liang X T. Effects of key parameters of straw chopping device on qualified rate, non-uniformity and power consumption. Int J Agric & Biol Eng, 2018; 11(1): 122–128.